Abundance and distribution of Roan Antelope (Hippotragus equinus) in the Old Oyo National Park, Nigeria (2013)
Knowledge of population size and structure is essential for the development of effective management strategies for animal populations. The abundance and distribution of Roan Antelope (Hippotragus equinus) in Old Oyo National Park during the dry season (between December, 2008 and February, 2009) were investigated. Stratified sampling was used to assign nine transects each 3km long in four major vegetation communities within the Park. The communities were Riparian grassland, Mixed open savannah woodland, Dense wooded and Outcrop. The transects were traversed twice a week between December and February and estimates were based on direct ensuring techniques. The study estimated 88 Roan Antelopes for the Park and. though small, has a viable structure for expansion. Riparian grassland had the highest proportion (44.32%) of the species while, the Outcrop vegetation type had the lowest (6.82%). The population density was 0.035 km2 while the biomass was 9.196 kg km-2. Horizontal distribution of the animal within the Park showed that the Roan Antelopes can be found between 8019'27.8"Nto 8025'16.2"Nand3047'0.3"E to 3049'17.9"E. The vertical distribution revealed that they occur between Altitudes 2 74m and 307m above sea level. Strict adherence to the fire regime of the Park, provision of water holes to increase home range, periodic monitoring of the population of the animal, and intensified efforts to guard against poachers have been suggested for the effective management of this species in the Old Oyo National Park.